Connections between the Levant and the Balkans in the late Middle Pleistocene: Archaeological findings from Velika and Mala Balanica Caves (Serbia). Issue 163 (February 2022) - Mihailović, Dušan; Kuhn, Steven L.; Bogićević, Katarina; Dimitrijević, Vesna; Marín-Arroyo, Ana B.; Marković, Jelena; Mercier, Norbert; Mihailović, Bojana; Morley, Mike W.; Radović, Predrag; Rink, William J.; Plavšić, Senka; et al.
Abstract: Major changes in the technological, economic, and social behavior of Middle Pleistocene hominins occurred at the onset of the Middle Paleolithic, 400–200 ka. However, until recently it was not possible to establish when, where, and how certain forms of Middle Paleolithic behavior appeared and spread into Southeastern Europe, mainly owing to gaps in the Paleolithic record. Here we report new results of dating, material culture, and the archaeological context of finds from the Balanica Cave Complex in Sićevo (Serbia). Two methods—thermoluminescence and electron spin resonance—were used to date the sequence. The geoarchaeological context was examined through sedimentology, micromorphology, and spatial analysis. Microfaunal remains were used to constrain the dates within an ecological zone, whereas macrofauna was analyzed for taxonomy and taphonomy to examine the source of accumulation and hominin behavior. Technological and typological features of the lithic assemblage were used to characterize lithic production at the site. Materials recovered from Layer 3 in Velika Balanica and from Layer 2 in Mala Balanica, both dated to MIS 9–7, include a distinctive set of archaeological assemblages which resemble contemporaneous Yabrudian assemblages from the Levant in important ways, and which are unlike contemporary material from the surrounding regions. In Velika Balanica, the lithic assemblages are associated with a large fireplace containing evidence of human activities similar to those from Qesem Cave (Israel). Dental remains uncovered in the same layer are consistent with Neanderthals. These findings suggest that the end of the Middle Pleistocene (before 300–240 ka) saw population movement and/or cultural transmission between Southwest Asia and the Balkans, which led eventually to a transfer of technology between Middle Eastern and European hominin populations and contributed to the shaping of Neanderthal behaviors throughout the eastern and northern Mediterranean.